PENGARUH GAYA KEPEMIMPINAN SUPORTIF, KOMUNIKASI HORIZONTAL DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN KONTRAK (Studi Pada Karyawan Frontliner PT. Bank Central Asia Tbk Banjarmasin) - Hadi Suyono; Dahniar; Tinik Sugiati (Universitas Lambung Mangkurat, 2019)
This study aims to identify and analyze the influence of supportive leadership style (X1), horizontal communication (X2), and career development (X3) as independent variables, either simultaneously or partially on contract employees’ job satisfaction of the frontline section (Y) as the dependent variable in PT. Bank BCA Tbk Banjarmasin.The type of the research is explanatory research. Unit analyzed are PT. Bank Central Asia Tbk in Kalimantan Selatan. The total population were 91 people and 41 people were selected as the sample. The sampling technique used was purposive sampling. The variables were measured by Likert scale. F test was used to analyze the influence of variables X1, X2, X3 to Y simultaneously and t test was used to analyze the effect of the variables partially. The multiple linear regressions were used as the analysis technique.The research concludeed that there is a simultaneously and partially effect of supportive leadership style (X1), horizontal communication (X2), and career development (X3) on contract employees’ job satisfaction of the frontline section in PT. Bank Central Asia Tbk Banjarmasin.